1994
DOI: 10.1111/j.2042-7158.1994.tb05705.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preservatives on Systemic Delivery of Insulin by Ocular Instillation in Rabbits

Abstract: The effects of absorption promoters and ophthalmic preservatives on the systemic absorption of insulin through the ocular route were investigated in albino rabbits. Insulin absorption was evaluated by its hypoglycaemic response. Although ocular instillation of insulin alone did not decrease the serum glucose concentration, instillation of insulin with absorption promoters such as EDTA and saponin decreased it. The promoting effect depended on the concentration of the absorption promoters. Of ophthalmic preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…They were previously reported to be effective for the corneal penetration of various drugs at those concentrations without severe toxicity. 6,7,13,17) The ingredients decreased TEER. The electrophysiological method enables evaluation of the change of the paracellular pathway transiently.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…They were previously reported to be effective for the corneal penetration of various drugs at those concentrations without severe toxicity. 6,7,13,17) The ingredients decreased TEER. The electrophysiological method enables evaluation of the change of the paracellular pathway transiently.…”
Section: Resultsmentioning
confidence: 98%
“…Newton et al 5) reported that Azone, a transdermal absorption enhancer, increased the ocular delivery of instilled cyclosporine and enhanced immunosuppression activity. We previously reported that ocular absorption of insulin was increased by ethylenediaminetetraacetic acid (EDTA) and benzalkonium chloride (BK), 6) and corneal penetration of sorbitol was improved by EDTA and chlorhexidine acetate. 7) The paracellular pathway can be monitored in real time by continuous measurement of the electrophysiological property of the cornea.…”
mentioning
confidence: 99%
“…The pharmaceutical aspects of these eyedrops, such as the absorption site for insulin, 1 the role of absorption enhancers, [1][2][3][4][5][6][7][8][9][10] and the correlation between its pharmacokinetics and pharmacodynamics, 1,10 have been well established. The latter allows scientists to easily quantitate the release of insulin by monitoring the changes in blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of MP and PP has been reported to enhance the corneal permeation of insulin, a peptide. 19) SMS is used as antioxidant and has also got preservative action. Addition of SMS or EDTA to diclofenac ophthalmic solution 0.1% (w /v) was also found to signiˆcantly increase the permeation.…”
Section: Resultsmentioning
confidence: 99%